Fasciotomy for Compartment Syndrome - Alfonsius Stefano (Cermin Dunia Kedokteran, 2023)
Compartment syndrome is an orthopedic emergency due to its potential complications and mortality. Many studies have discussed the supporting examination and closure of phasiotomy wounds related to compartment syndrome, but there is still no agreed reference standard for additional diagnostic tool and fasciotomy management. Surgeon's experience and preference are important in the management of compartment syndrome.   Sindrom kompartemen merupakan salah satu kegawatdaruratan ortopedi karena potensi komplikasi dan risiko kematiannya. Banyak penelitian yang membahas mengenai pemeriksaan penunjang dan penutupan luka fasiotomi terkait sindrom kompartemen, namun belum ada referensi yang disetujui sebagai baku standar. Pengalaman dan preferensi dokter bedah terkait merupakan unsur terpenting dalam tata laksana sindrom kompartemen.